Erzbischof Hinkmar und die Folgen Der vierhundertjährige Weg historischer Erinnerungsbilder von Reims nach Trier - Schneider, Olaf (Millennium-Studien / Millennium Studies, 2010)
The present study is concerned with sources for the history of the dioceses of Reims and Trier since the 8th century. It starts with essential information on the history of these dioceses in the Early Middle Ages which can be traced back mainly to accounts by the influential Archbishop Hinkmar of Reims (845-882). The problems of Hinkmar`s accounts and their continued influence are brought out against the contemporary background of the age of their composition, and their later deformations are followed over time. By taking up the trail of these deformations, the contingency of historical information and transmission becomes clear.